Isospin amplitudes in [lambda]0b → J/[psi lambda] ([sigma]0) and [xi]0b → J/[psi xi]0 ([lambda]) decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Physical review letters, 2020)
Ratios of isospin amplitudes in hadron decays are a useful probe of the interplay between weak and strong interactions and allow searches for physics beyond the standard model. We present the first results on isospin amplitudes in b-baryon decays, using data corresponding to an integrated luminosity of 8.5 fb−1, collected with the LHCb detector in pp collisions at center of mass energies of 7, 8, and 13 TeV. The isospin amplitude ratio |A1(Λ0b→J/ψΣ0)/A0(Λ0b→J/ψΛ)|, where the subscript on A indicates the final-state isospin, is measured to be less than 1/21.8 at 95% confidence level. The Cabibbo suppressed Ξ0b→J/ψΛ decay is observed for the first time, allowing for the measurement |A0(Ξ0b→J/ψΛ)/A1/2(Ξ0b→J/ψΞ0)|=0.37±0.06±0.02, where the uncertainties are statistical and systematic, respectively.
Im Titel sind lambda, psi, sigma und xi als griechische Buchstaben dargestellt
Im Titel ist die Ziffer "0" hochgestellt und der Buchstabe b tiefgestellt
LHCb Collaboration*: Roel Aaij, Flavio Archilli, Sebastian Bachmann, Daniel Berninghoff, Martino Borsato, David Gerick, Jascha Grabowski, Paul André Günther, Xiaoxue Han, Stephanie Hansmann-Menzemer, Jiangqiao Hu, Renata Kopecná, Blake Leverington, Hanna Malygina, Jörg Marks, Alessio Piucci, Ulrich Uwer, Lukas Witola, Alexey Zhelezov [und 889 weitere]
Gesehen am 30.09.2020